Carbon and methane cycling in arsenic-contaminated aquifers. (15th July 2021) - Stopelli, Emiliano; Duyen, Vu T.; Prommer, Henning; Glodowska, Martyna; Kappler, Andreas; Schneider, Magnus; Eiche, Elisabeth; Lightfoot, Alexandra K.; Schubert, Carsten J.; Trang, Pham K.T.; Viet, Pham H.; Kipfer, Rolf; et al.
Highlights: Comprehensive carbon isotope analyses for δ 13 C-DOC, δ 13 C-DIC and δ 13 C-CH4 provide novel insights. Occurrence of fermentation, methanogenesis and methanotrophy was identified. Locally depositional organic matter promotes methanogenesis and very high As concentrations. Methane cycling could play an overlooked role in many high-As aquifers around the world. Identified processes are triggers for the elusive heterogeneity of As concentrations in groundwater. Abstract: Geogenic arsenic (As) contamination of groundwater is a health threat to millions of people worldwide, particularly in alluvial regions of South and Southeast Asia. Mitigation measures are often hindered by high heterogeneities in As concentrations, the cause(s) of which are elusive. Here we used a comprehensive suite of stable isotope analyses and hydrogeochemical parameters to shed light on the mechanisms in a typical high-As Holocene aquifer near Hanoi where groundwater is advected to a low-As Pleistocene aquifer. Carbon isotope signatures ( δ 13 C-CH4, δ 13 C-DOC, δ 13 C-DIC) provided evidence that fermentation, methanogenesis and methanotrophy are actively contributing to the As heterogeneity. Methanogenesis occurred concurrently where As levels are high (>200 µg/L) and DOC-enriched aquitard pore water infiltrates into the aquifer. Along the flowpath to the Holocene/Pleistocene aquifer transition, methane oxidation causes a strong shift in δ 13 C-CH4 from -87‰ to +47‰, indicating high reactivity. These findings demonstrate a previously overlooked role of methane cycling and DOC infiltration in high-As aquifers. Graphical abstract: Image, graphical abstract